Lorenz ordering of order statistics from log-logistic and related distributions - Christian Kleiber (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2002)
This paper obtains Lorenz ordering relationships among order statistics from log-logistic samples of possibly different sizes. Some results extend other families including the Lomax, Burr III and Burr XII distributions.
Keywords: 519; k-out-of-n systems; order statistics; Lorenz order; (generalized) log-logistic distributions